Kingdom of Lesotho : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2005)
The Kingdom of Lesotho's 2005 Article IV Consultation reports that the government's fiscal position and the external current account have improved markedly. The authorities are preparing an action plan, in collaboration with development partners, to improve the business climate. Critical measures aim to increase labor productivity through training, reduce domestic costs for the private sector by addressing infrastructure bottlenecks, remove regulatory and administrative impediments, improve access to financial services, and promote product and export market diversification.